L’alimentation hydraulique de Saint-Romain-en-Gal (Rhône), quartier de Vienne antique (Isère) - Laurence Brissaud; Jean-Luc Prisset (Gallia)
Vienne/Vienna is a duplex urbs which developed on both banks of the Rhône between the middle of the 1st century AD and the end of the 3rd century AD. The information collected on each of these banks, in Vienne, Saint-Romain-en-Gal and Sainte-Colombe (France), provide different but nevertheless complementary information on the water supply in one of the most important cities in Gaul.On the left bank, the river Gère made its way through the hills. It marked the northern limit of the original town, which grew at the foot of steep hills. The built-up area was delimited to the west by the river and to the south by two streams, the Saint-Marcel and the Saint-Gervais. In the middle of the 1st century AD, the city began to expand on the right bank, mainly along a path that crosses the valley from east to west. This was established north of the mouth of the Gère. The river then must have been crossable with a ferry, or even via a ford when water levels were low.The remains of six aqueducts have been observed on the left bank of the Rhône. Five of them, A to E, followed the Gère valley at similar altitudes to the centre of town. The sixth, the F, was the longest. It was established at a higher altitude and circumvented the hills to end above the Saint-Gervais stream. The chronologies of the construction of these structures, all underground, are not known. Only the construction of the one with the largest section, the E, has been dated to the 20-30s AD. For its part, the development of aqueduct B was subsequent to the construction of conduits C and D because it reused sections of them on its route.On the right bank of the Rhône, a relatively large plain occupies the inside curve of the river, limited to the west by a continuous slope, likely punctuated by streams with moderate flows. The only notable river marks the southern limit of this plain. No vestige of an aqueduct has been observed since an 18th century mention that indicated the presence of two conduits west of Sainte-Colombe.At the site of the archaeological site of Saint-Romain-en-Gal, there are clear signs of the presence of a stream and a ditch. They would then have been absorbed or integrated into the urban structure that developed from the Augustan era onwards. At this time, the water supply relied on wells and presumably on catchments of water from some streams.From the time of Tiberius/Claudius, the picture changes. Numerous wooden and lead pipes appear in the Saint-Romain-en-Gal district, while on the left bank of the Rhône several inscriptions mention the endowment of an aqueduct by two quattvorvir. Half the inscriptions were found north of the Gère, which indicates that the land on its right bank was supplied with water. The route of an aqueduct can be reconstructed from an 18th century reference and from the topography of the hill. This aqueduct may have also contributed to supplying the Saint-Romain-en-Gal district by means of a bridge over the Rhône constructed at the same time.The evolution of urban development on the right bank of the Rhône indicates that water supply from the left bank was the rule until the end of the 2nd century AD. However, this does not preclude the use of the left bank’s resources, in particular for buildings located at the foot of the hillside. The archaeological site also provides many possibilities for exploring changes in the mode of water distribution in neighbourhood centres. To this end, the combined study of hydraulic facilities and roads has proven essential. It is hoped that such studies could be carried out on the left bank to find out about hydraulic organization in the town centre and the links that connected aqueducts on the left bank and pressurised water systems on the right bank.